The Contestation of Hadith Memes on the Prohibition of Music - Syahridawaty, Syahridawaty; Qudsy, Saifudin Zuhri (Journal of Hadith Studies, 2019)
The contestation of prohibition of music that has been happening in the offline world is now reaching the online world. The group that has been emphasizing the prohibition of music in the offline world, and becomes a minority group, precisely in the online world this group dominates. One of the groups that emphasize prohibition of music and dominates in the online world is the Salafi group. This group formed an Islamic study on social media, such as Facebook which was named after the Kajian Islam-Sunnah. This paper aims to examine the forms of contestation about the prohibition of music in the Kajian Islam-Sunnah group and its responds for netizens. By using the theory of contestation and discourse analysis, this study finds that the contestation on prohibition of music that occurs in the Kajian Islam-Sunnah group appears from several types of memes displayed. Each meme contains an argument on the prohibition of music by citing the hadith and muslim scholars. This contestation happens for the differences in understanding between the two parties, the parties agreeing and disagreeing about the prohibition of music. The majority of those who agree are from the Salafi group, while those who disagree are from the non-Salafi group.